ANALYZING LAND ACQUISITION LEGISLATION IN DEVELOPING ECONOMIES: STRIVING FOR EQUITABLE PUBLIC INTEREST AND HUMAN RIGHTS - Tabiu, Heryanti (American Journal of Legal Practice (AJLP), 2023)
Land acquisition for public interest is a vital component of development activities, particularly in developing countries. However, it remains a contentious issue due to its potential impact on human rights and legal land ownership rights. Conflicts between the government and landowners frequently arise during land acquisition for public interest purposes, leading to violations of human rights. This paper critically reviews the laws and policies governing land acquisition in developing countries and examines their effectiveness in balancing public interest and human rights. The paper argues that many developing countries have failed to strike a balance between these two interests, leading to widespread human rights violations during land acquisition processes. Using empirical evidence from various case studies, the paper highlights the importance of a just and fair approach to land acquisition that respects the human rights of those affected. The paper concludes by offering recommendations for improving the legal and policy frameworks governing land acquisition in developing countries to promote greater respect for human rights in such processes